Study of Red-mechanical cement compressive strength of bricks made from clay mixtures Portland (Nexo Revista Científica, 2014)
A proposal for the development of handcrafted bricks of clay soil stabilized with gray portland cement, as an alternative to reduce the level of pollution caused by emissions of carbon dioxide from the use of wood as a source of combustion during the baking step of bricks is presented. The work was carried out in the soil bank of one brickyard located in La Paz Centro, Nicaragua. Moreover, two different brands of Portland cement were used. Cement/soil samples were prepared according to the established norms, and the mechanical-physical properties were compared with bricks cooked through a full mixed factorial design experiment. The parameters studied were ratios of cement /soil, water /cement binder and cement brand. The best results for samples of cement/soil reached resistances higher than 12 MPa after 28 days of curing and absorption percentages lower than 15%. Hydration products, responsible for the development of mechanical strength, were analyzed using infrared spectroscopy. The largest number of hydrated calcium silicate was obtained for samples with Canal cement. DOI: http://dx.doi.org/10.5377/nexo.v27i2.1945